ANALISIS PENGARUH NET PROFIT MARGIN, RETURN ON ASSETS, DEBT TO EQUITY RATIO, RETURN ON EQUITY DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
The  objective  of  the  study  is  to  examine  the  effect  ofNet Profit Margin (NPM), Return on Assets (ROA), Debt to Equity Ratio (DER), Return on Equity (ROE) and Current Ratio (CR)on Stock Prices. This study was taken because there are still differences between the research study with each other. This research was conducted using secondary data. Population in this research was  insurance  company  obtained  from  share  which  was  listed  and  “go  public”  in Indonesian Stock Exchage period 2010-2012. Sampling technique used was purposive sampling. There is 70 companies that can be analysed. This study is analyzed by using multiple regression. The  multiple  regression  shows  that Net Profit Margin significant positive effect on stock price, Return on Assets significant positive effect on stock price, Debt to Equity Ratio haven’t significant positive effect on stock price, Return on Equity haven’t significant negative effect on stock price, and  Current Ratio haven’t significant positive effect on stock price. Keywords: NPM, ROA, DER, ROE and Stock Price